Riemann-Stieltjes operators between Bergman-type spaces and α-Bloch spaces - Songxiao Li (International Journal of Mathematics and Mathematical Sciences)
We study the following integral operators: Jgf(z)=∫0zf(ξ)g′(ξ)dξ; Igf(z)=∫0zf′(ξ)g(ξ)dξ, where g is an analytic function on the open unit disk in the complex plane. The boundedness and compactness of Jg, Ig between the Bergman-type spaces and the α-Bloch spaces are investigated.